Acidic Versus Alkaline Bacterial Degradation of Lignin Through Engineered Strain E. coli BL21(Lacc): Exploring the Differences in Chemical Structure, Morphology, and Degradation Products - Morales, Gabriel Murillo; Ali, Sameh S.; Si, Haibing; Zhang, Weimin; Zhang, Rongxian; Hosseini, Keyvan; Sun, Jianzhong; Zhu, Daochen (Frontiers in Bioengineering and Biotechnology, 2020)
There is increasing interest in research on lignin biodegradation compounds as potential building blocks in applications related to renewable products. More attention is necessary to evaluate the effects of the initial pH conditions during the bacterial degradation of lignin. In this study we performed experiments on lignin biodegradation under acidic and mild alkaline conditions. For acidic biodegradation, lignin was chemically pretreated with hydrogen peroxide. Alkaline biodegradation was achieved by developing the bacterial growth on Luria and Bertani medium with alkali lignin as the sole carbon source. The mutant strain E.coli BL21 (Lacc) was used to carry out lignin biodegradation over 10 days of incubation. Results demonstrated that under acidic conditions there was a predominance of aliphatic compounds of the C3-C4 type. Alkaline biodegradation was produced in the context of oxidative stress, with a greater abundance of aryl compounds. The final pH values of acidic and alkaline biodegradation of lignin were 2.53 and 7.90, respectively. The results of the gas chromatography mass spectrometry analysis detected compounds such as crotonic acid, lactic acid and 3-hydroxybutanoic acid for acidic conditions, with potential applications for adhesives and polymer precursors. Under alkaline conditions, detected compounds included 2-phenylethanol and dehydroabietic acid, with potential applications for perfumery and anti tumor/anti-inflammatory medications. Size-exclusion chromatography analysis showed that the weight-average molecular weight of the alkaline biodegraded lignin increased by 6.75-fold compared to the acidic method, resulting in a repolymerization of its molecular structure. Lignin repolimerization coincided with an increase in the relative abundance of dehydrobietic acid and isovanillyl alcohol, from 2.70% and 3.96% on day zero to 13.43% and 10.26% on day 10. The results of the Fourier-transformed Infrared spectroscopy detected the presence of C = O bond and OH functional group associated with carboxylic acids in the acidic method. In the alkaline method there was a greater preponderance of signals related to skeletal aromatic structures, the amine functional group and the C – O – bond. Lignin biodegradation products from E.coli BL21 (Laccase), under different initial pH conditions, demonstrated a promising potential to enlarge the spectrum of renewable products for biorefinery activities.